Effects of Avatar Race in Violent Video Games on Racial Attitudes and Aggression. (August 2014) - Yang, Grace S.; Gibson, Bryan; Lueke, Adam K.; Huesmann, L. Rowell; Bushman, Brad J.
The media often link Black characters and violence. This is especially true in video games, in which Black male characters are virtually always violent. This research tested the effects of playing a violent game as a Black (vs. White) avatar on racial stereotypes and aggression. In Experiment 1, White participants ( N = 126) who played a violent video game as a Black avatar displayed stronger implicit and explicit negative attitudes toward Blacks than did participants who played a violent video game as a White avatar or a nonviolent game as a Black or White avatar. In Experiment 2, White participants ( N = 141) who played a violent video game as a Black (vs. White) avatar displayed stronger implicit attitudes linking Blacks to weapons. Implicit attitudes, in turn, related to subsequent aggression. Black violent video game avatars not only make players more aggressive than do White avatars, they also reinforce stereotypes that Blacks are violent.